Metabolomic Profiling and Cytotoxic Tetrahydrofurofuran Lignans Investigations from Premna odorata Blanco - Abeer H. Elmaidomy; Rabab Mohammed; Hossam M. Hassan; Asmaa I. Owis; Mostafa E. Rateb; Mohammad A. Khanfar; Markus Krischke; Martin J. Mueller; Usama Ramadan Abdelmohsen (Metabolites, 2019)
Metabolomic profiling of different Premna odorata Blanco (Lamiaceae) organs, bark, wood, young stems, flowers, and fruits dereplicated 20, 20, 10, 20, and 20 compounds, respectively, using LC−HRESIMS. The identified metabolites (1−34) belonged to different chemical classes, including iridoids, flavones, phenyl ethanoids, and lignans. A phytochemical investigation of P. odorata bark afforded one new tetrahydrofurofuran lignan, 4β-hydroxyasarinin 35, along with fourteen known compounds. The structure of the new compound was confirmed using extensive 1D and 2D NMR, and HRESIMS analyses. A cytotoxic investigation of compounds 35−38 against the HL-60, HT-29, and MCF-7 cancer cell lines, using the MTT assay showed that compound 35 had cytotoxic effects against HL-60 and MCF-7 with IC50 values of 2.7 and 4.2 µg/mL, respectively. A pharmacophore map of compounds 35 showed two hydrogen bond acceptor (HBA) aligning the phenoxy oxygen atoms of benzodioxole moieties, two aromatic ring features vectored on the two phenyl rings, one hydrogen bond donor (HBD) feature aligning the central hydroxyl group and thirteen exclusion spheres which limit the boundaries of sterically inaccessible regions of the target’s active site.